Author Correction: Observation of a robust and active catalyst for hydrogen evolution under high current densities (Nature Communications, (2022), 13, 1, (7784), 10.1038/s41467-022-35464-2) - Zhang, Yudi; Arpino, Kathryn E.; Yang, Qun; Kikugawa, Naoki; Sokolov, Dmitry A.; Hicks, Clifford W.; Liu, Jian; Felser, Claudia; Li, Guowei (Nature Communications, 2023)
In this article the affiliation details for Naoki Kikugawa were incorrectly given as ‘Max Planck Institute for Chemical Physics of Solids, Nöthnitzer Strasse 40, 01187, Dresden, Germany’ but should have been ‘National Institute for Materials Science (NIMS), Tsukuba, 305-0003, Japan’. The original article has been corrected.
CRIS-Team Scopus Importer:2023-03-20